Investigating a soluble pharmaceutical salt: Albendazole Hydrochloride - Bongioanni, Agustina (2019)
Albendazole is an effective antihelmintic drug, which has an unpredictable therapeutic response due to its low solubility in biological fluids that limits its oral absorption. In an attempt to improve solubility, albendazole hydrochloride, a soluble pharmaceutical salt, was obtained and characterized by X-ray diffraction together with magic angle spinning solid-state nuclear magnetic resonance spectroscopy, Raman and Fourier transform infrared spectroscopies, thermal analysis, energy-dispersive X-ray spectroscopy, and scanning electron microscopy. These studies revealed that the crystalline habit of albendazole hydrochloride is different from that of the albendazole solid forms previously reported. The full structure was elucidated by performing single-crystal X-ray diffraction. The characterization studies showed the participation of the carbamate moiety in the salt formation. In addition, the solubility studies showed a significant increase in the solubility with respect to forms I and II of albendazole. In conclusion, our results indicate that albendazole hydrochloride can be an auspicious salt to be used as a new product in an attempt to counteract unfavorable pharmaceutical properties.